(untitled) (Texas Journal of Philology, Culture and History, 2024)
Segmental phonostylistics, as a field of linguistics that studies the stylistic functions of individual sounds (phonemes) and their combinations (phoneme sequences) in speech, is an integral part of phonetic analysis. Understanding the stylistic functions of segments is necessary for a deep understanding of both oral and written speech, since the sound form of a word can significantly influence its perception and interpretation. In this article we will focus on how the stylistic features associated with segmental phonostylistics are reflected in the dictionaries of three languages with different phonological systems and lexicographical traditions: English, Russian and Karakalpak